Granuloma formation in leishmaniasis: A mathematical model. (7th January 2017) - Siewe, Nourridine; Yakubu, Abdul-Aziz; Satoskar, Abhay R; Friedman, Avner
Abstract: Leishmaniasis is a disease caused by the Leishmania parasites. The two common forms of leishmaniasis are cutaneous leishmaniasis (CL) and visceral leishmaniasis (VL). VL is the more severe of the two and, if untreated, may become fatal. The hallmark of VL is the formation of granuloma in the liver or the spleen. In this paper, we develop a mathematical model of the evolution of granuloma in the liver. The model is represented by a system of partial differential equations and it includes migration of cells from the adaptive immune system into the granuloma; the rate of the influx is determined by the strength of the immune response of the infected individual. It is shown that parasite load decreases as the strength of the immune system increases. Furthermore, the efficacy of a commonly used drug, which increases T cells proliferation, increases in an individual with stronger immune response. The model also provides an explanation why, in contrast to humans, mice recover naturally from VL in the liver. Abstract : Highlights: As the parameter that gauges the strength of the immune response, β, increases, the proportion of Leishmania parasites to macrophages decreases. For humans with normal healthy immune system, the parameter β varies in the range 31 < β < 62 ; for any β in this range, infected humans will die if untreated, but will recover if treated. The efficacy of a drug (such as SAG) decreases as β increases in the range 10 < β < 140 . However, SAG may have negative side-effects such as nausea, vomiting, diarrhea, dizziness and anaphylaxis which leads to low blood pressure and may cause death. Hence, there is a need to weigh the benefits of increasing the amount of drug (above the MTD) versus the possibility of life threatening side-effects.